PENGARUH PENDAPATAN ASLI DAERAH DAN BELANJA MODAL TERHADAP KINERJA KEUANGAN PEMERINTAH - Maharani, Bintang; Puspitasari, Ayu; Yantiana, Nella (CV. Lafadz Jaya, 2024)
There is an increase and decrease in regional income experienced by West Kalimantan. The focus of this research is to analyze the impact of Regional Original Income and Capital Expenditure on the financial performance of the West Kalimantan regional government. Income serves as an indicator of regional financial capability, while capital expenditure measures the effectiveness of capital expenditure from fund allocation for infrastructure. Through multiple linear regression method, this research will reveal the extent to which these two factors affect the government's financial performance, providing insights for fiscal policy and regional financial management. The independent variables are Regional Original Income and Capital Expenditure. Secondary data is obtained from the Regional Financial Statements of the West Kalimantan Provincial Government. The population is the West Kalimantan Province. Sample selection is conducted using purposive sampling technique with a sample size of 69. The analysis techniques include descriptive statistical tests, classical assumptions, model accuracy, and multiple linear regression analysis using SPSS 26. The research findings indicate that there is a positive influence on the government's financial performance by Regional Original Income. Government's financial performance is not affected by Capital Expenditure.